EVENT STRATIGRAPHY AND CORRELATION PROBLEMS OF THE ORDOVICIAN STRATA OF GORNY ALTAI AND SALAIR - N. V. Sennikov; O. T. Obut; E. V. Lykova; A. V. Timokhin; R. A. Khabibulina; T. A. Shcherbanenko (Геодинамика и тектонофизика)
Study of the Ordovician sedimentary sequences of Gorny Altai and Salair has revealed lithological and paleontological features correlating with global sedimentary events:(1) The Acerocare Regressive Event (an initial event in the Early Tremadocian);(2) Black Mountain Transgressive Event (Early Tremadocian);(3) Peltocare Regressive Event (Tremadocian);(4) Kelly Creek Regressive Event (Late Tremadocian);(5) Ceratopyge Regressive Event (Late Tremadocian);(6) Billingen Transgressive Event (Early Floian);(7) Stein Lowstand Event (Middle Darriwilian);(8) Vollen Lowstand Event (Sandbian);(9) Arestad Drowning Event (Middle Sandbian);(10) Frognerkilen Lowstand Event (Early Katian);(11) Linearis Drowning Events 1 and 2 (Middle Katian);(12) Terminal Husbergoya Lowstand Event (Hirnantian); and(13) Hirnantian Lowstand Event (HICE) (Late Ordovician).The chronostratigraphic levels with traces of the global sedimentary events in the Uymen-Lebed structural-facies zone (SFZ) (Gorny Altai) differ from those in the Charysh-Inya and Anui-Chuya SFZ (Altai). In the Ordovician, the Altai basin located in the Charysh-Inya and Anui-Chuya SFZ was a marine area separated from both the Uymen-Lebed basin and the coeval Salair basin. The traces of the global sedimentary and/or biotic events in the Altai and Salair sections can be used as a precise basis for direct correlation of the local stratigraphic units with the units of the International Stratigraphic Chart.